Cyberbullying and Empathy in the Age of Hyperconnection: An Interdisciplinary Approach - Auriemma, Vincenzo; Iorio, Gennaro; Roberti, Geraldina; Morese, Rosalba (Frontiers in Sociology, 2020)
Considering cyberbullying as a new frontier of analysis, we find ourselves today with the duty to analyze it within a much wider social complex. Today, unlike yesterday, we no longer have to dwell on the classic exclusion logics, but and starting from those exclusion logics that Didier Bigo (Bigo, 2008) underlined a few years ago, we must enter and analyze them. In fact, we live more and more often in a thin line of excluded/excluded (the very old victim/executioner dichotomy evolves into the headless mass of the internet of things). Trying to amplify, but at the same time simplify, this dichotomy, we can say that today we live in the era of the so-called ban-opticon, or the logic of banning, it goes from the simple exclusion of friendship on the net (Facebook) up to exclusion in a game of video games (for example within the narrow circle of friendship of the PlayStation) or, even worse, of knowledge. The present review focused on discussion of cyberbullying applying an interdisciplinary approach from sociology to psychology with the analysis of important aspect such as empathy, hyperconnection, individualization. The concept of empathy has been studied several times since Weber (Weber, 1922). In fact, between the late nineteenth and early twentieth centuries, small and sporadic investigations into the Einfühlung and empathy began to emerge in the doctrines. And none of what emerged today was present within the works on sympathy carried out, in the eighteenth century, by Hume (1711 - 1776) and Smith (1723 - 1790) (Hume, 1740, p. XXXI); (Smith, 1759, p. II-III). Initially, as Jeremy Rifkin (1945) describes in his text The Civilization of Empathy, the term Empathy was used to describe sympathy or compassion. To conclude, we analyzed all those relational plots, of the trans-historical narrative identities that are outside their own habitat but that in any case influence it. The interdisciplinary approach allows a broader and more innovative analysis to better understand the phenomenon of Cyberbullying and to conceptualize new intervention strategies in the social and educational field and to open new frontiers in research.